Isolation and Phylogenetic Analysis of Atypical Porcine Pestivirus Isolates Identified in Russian Swine Herds - Afshona Anoyatbekova; Anton Yuzhakov (Viruses)
Atypical porcine pestivirus (APPV) was first identified in 2015 in North America by high-throughput sequencing. APPV is associated with congenital tremor A-II and is widely distributed worldwide. In this study, a total of 2630 samples of domestic pigs obtained from 14 regions of Russia from 2020 to 2024 were screened for APPV presence by qRT-PCR. APPV was detected in 12 farms located in eight regions. The overall positive rate was 8.8%. It has been established that APPV has been circulating in Russian swine herds since at least 2020. The phylogenetic analysis demonstrated that the Russian isolates are variable and assigned into three clusters. The isolates from the Krasnoyarsk Krai, Belgorod, Tomsk, and Kursk regions and the Republic of Buryatia share a high nucleotide identity (94.3–98.8%) with the Hungarian strains, while the isolates from the Moscow and Pskov regions share a nucleotide identity (89.2–94.3%) with strains from the USA. The isolate from the Republic of Mordovia has a high nucleotide identity (97.1%) with the South Korean strain. In vitro studies of the Russian isolates revealed the replication of the Belgorod 151 strain in SPEV cells. Thus, this is the first large-scale study that confirms the circulation of APPV in swine herds in Russia and describes its isolation in cell culture.